2012
DOI: 10.4104/pcrj.2012.00027
|View full text |Cite
|
Sign up to set email alerts
|

Spirometrically-defined restrictive ventilatory defect: population variability and individual determinants

Abstract: Background: A spirometrically-defined restrictive ventilatory defect is a common finding when performing spirometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 29 publications
6
35
1
1
Order By: Relevance
“…Participants in the US National Health and Nutrition Examination Survey (NHANES) with spirometric restriction were more likely to report functional impairment and fair/poor health than were participants with no lung disease and normal lung function [3,7], and the magnitude of these effects was largely comparable to that seen in subjects with moderate chronic obstructive pulmonary disease (COPD). Similarly, spirometric restriction was found to be associated with worse respiratory-specific health status, as assessed by the St George's Respiratory Questionnaire, in both the COPDGene [5] and Spanish EPI-SCAN [4] studies. However, to what extent the decreased health-related quality of life in spirometric restriction is dependent on the coexistence of respiratory symptoms and comorbidities remains to be determined.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Participants in the US National Health and Nutrition Examination Survey (NHANES) with spirometric restriction were more likely to report functional impairment and fair/poor health than were participants with no lung disease and normal lung function [3,7], and the magnitude of these effects was largely comparable to that seen in subjects with moderate chronic obstructive pulmonary disease (COPD). Similarly, spirometric restriction was found to be associated with worse respiratory-specific health status, as assessed by the St George's Respiratory Questionnaire, in both the COPDGene [5] and Spanish EPI-SCAN [4] studies. However, to what extent the decreased health-related quality of life in spirometric restriction is dependent on the coexistence of respiratory symptoms and comorbidities remains to be determined.…”
Section: Introductionmentioning
confidence: 85%
“…In recent years multiple population-based studies have shown that a significant proportion of the general adult population has a restrictive pattern on spirometry, characterised by reduced levels of forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC), and normal FEV1/FVC ratio [1][2][3][4]. Although the determinants and biological bases of this restrictive pattern remain largely unknown, subjects with spirometric restriction have been shown to be more likely to have cough and phlegm, shortness of breath with wheezing and dyspnoea [3,[5][6][7], and suffer from and die of a number of comorbidities, including coronary heart disease, hypertension, metabolic syndrome and diabetes [2,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Mannino et al comprising people age 40 years and above from 14 sites across different continents who took part in the Burden of Obstructive Lung Disease (BOLD) study, the prevalence of restrictive pattern defined by a ratio FEV1/FVC ≥70% and a FVC<80% varied from 6.1% in Sydney (Australia) to 29.3% in Cape Town (South Africa) and 45.9% in Manilla (Philippines) [21]. Soriano et al also found a point prevalence of 12.7% in subjects aged 40 years and above in Spain [22]. In the ≥40 years of age particpants in our study, the prevalence of restrictive pattern was 24.2% (LLN-based) and 20.1% (fixed cut-off based), which is closer to the South African figures in BOLD [21].…”
Section: Discussionmentioning
confidence: 99%
“…Further complicating the definition of emphysema is the reduction in FVC that can result from several disorders including obesity. 10,11 This dilemma makes mild COPD difficult to assess in these individuals with present definitions.…”
Section: Definition Of Early Copdmentioning
confidence: 99%